MEMAHAMI HUBUNGAN PARASOSIAL PADA PENGGEMAR STRAY KIDS (Studi Fenomenologi Pengguna Aplikasi Bubble For JYPNATION) - Sherina Aprillia Zahra, (2024)
Technological advances and innovation in the development of communication media, especially social media, make communication between fans and K-Pop idols easier. The interactions that occur begin to create a pseudo-relationship which is commonly known as a parasocial relationship. Currently, there are many platforms that support the occurrence of parasocial relationship, one of them is the Bubble For JYPNATION application. This research focuses on how Stray Kids fans use and interpret parasocial relationship while using the Bubble For JYPNATION application. The research uses a qualitative approach with transcendental phenomenology methods and constructivist paradigms. Data obtained through in-depth interviews, observation and documentation with informants who are Stray Kids fans who currently or have used the Bubble For JYPNATION application for at least one month's subscription, and have a Twitter / X account. Research results based on reasons for subscribing, reasons for choosing Stray Kids members to subscribe, available features, six levels of Hierarchy of Meaning, the process of Coordinated Meaning Management, and three phases of parasocial relationships show that interactions using the Bubble For JYPNATION application create meaning for fans. Where this is formed based on the feelings felt during the exchange of messages. Fans also feel like they know Stray Kids members more closely, although there is still a barrier between idols and fans. This meaning makes fans feel like they have a special relationship and it feels more real, and this relationship leads to a parasocial relationship. However, parasocial relationships only go through two phases. The parasocial relationships that occur also have a positive impact on fans.